Principals distributed leadership practice of school performance in junior high school (SMP) south Sulawesi Indonesia - Baharuddin, Usman; Daud, Khadijah Binti (International Journal for Innovation Education and Research, 2014)
This paper aims to identify the principals distributed leadership practice toward school performance in Junior High Schools, State of South Sulawesi, Indonesia by using quantitative methods. Quantitative data obtained from the questionnaire interviews of 540 respondents from among the teachers. There are four dimensions required for Junior High School principals derived from questionnaire data with the respondent that the vision mission and goals of the school, the school culture, the sharing of responsibilities and leadership practices. The results showed that the culture of the school is the most dominant dimension that can affect school performance and distributed leadership has positive relationship in improving school performance. This means that if the principals perform well in school leadership the school performance can also be improved. Dimensions must be available on the school principals themselves to discharge their duties, especially in leadership activities to improve the performance of schools in South Sulawesi.